Relações hipsométricas e classificação da capacidade produtiva de Eucalyptus urophylla, na região do Jari, no Pará - SILVA, Marcela Aranha da (2019)
The objective of this work was to evaluate linear models for modeling hypsometric relationships and to evaluate two different methods for classifying the productive capacity of a Eucalyptus urophylla stand. Three linear models were estimated to estimate the hypsometric relationships and two methods for site classification. The data come from an unclassified clonal planting of Eucalyptus urophylla, belonging to Jari Celulose Papel and S /A (Jari Florestal and Agropecuária). Three linear models were tested, where total height (Ht) was used as the dependent variable and the breast height diameter (DAP) was used as the independent variable. The linear regression technique was applied by the least squares method to the three models tested. To generate the site index curves the Schumacher model was adjusted for the Guidance Curve and Equation of Differences methods. The models tested in this work were evaluated with the statistics: standard error of the percentage estimate (Syx%), adjusted coefficient of determination (R²ajust) and with the graphical distribution of the residues. According to the statistical analyzes of the models, for the estimation of height growth, the Stofels model was superior in relation to the other two adjusted models, with R2 0,8006 and Sxy 11,92%. For the classification of productive capacity, the Guide Curve method presented R2 0.8943 and Sxy 6.73%, so it obtained a better precision in comparison with the method of the difference equation. Thus, the model chosen to estimate Ht was the Stofels model and the Guide Curve method was chosen to explain the productive capacity.